INFLUENCE OF PSYCHOPHYSIOLOGICAL FEATURES ON THE CONDITION OF TEETH HARD TISSUES AND PERIODONTIUM IN YOUNG SUBJECTS - Vadzyuk, S.N.; Boliuk, Yu.V.; Luchynskyi, M.A. (World of Medicine and Biology, 2019)
The article presents data on the correlation between the indices of assessment of soft teeth deposits, dental calculus, the state of teeth hard tissues, periodontium and psychophysiological characteristics in subjects aged 18-23 with periodontopathology. The significant influence of the amount of dental calculus and retention factors on the intensity of the inflammatory process in periodontal tissues was revealed. However, the dependence of these local factors and values of the Schiller-Pisarev test and the papillary-marginal-alveolar index from the oral hygiene state has not been determined. In addition, data on the relationship between the intensity of inflammation and the indicators for evaluating the signs of neurotic depression, asthenia, aggressiveness and frustration were obtained.